Inequality of Sexual Violence Reporting in Online Media during the New Normal Era: A Feminist Perspective - Khasanah, Noor Lailatul; Marfu'ah, Usfiyatul; Musyafak, Najahan; Rahayani, Yayan (UIN Sunan Kudus, 2023)
Issues of sexual violence have been reported as imbalanced by online media. This imbalance can be seen in the media's intensity, object, and motives for writing the news. This tendency indicates that the media is still taking sides in disclosing the incidents of sexual violence that occurred. The purpose of this study is to complement the findings of previous studies by focusing on how online media reports of sexual violence issues. This study uses a descriptive qualitative research based on content analysis through a feminist approach. Data was obtained through primary and secondary sources. Primary data is obtained from 5 online mainstream media selected using purposive sampling. The five media are cnnindonesia.com; Detik.com; Kompas.com; Tempo.co, and Tribun.com. At the same time, secondary data was obtained from online sources from several sites related to the research theme, including the Press Council, the Indonesian Broadcasting Commission, the Ministry of Women's Empowerment and Children Protection, and the National Commission for Women. This study focuses on three months between January – March 2022 to investigate news about sexual violence in online media. The results of this study indicate that first, the high incidence of violence during the three months reached 119 reports. Second, in writing essays, the media tend to lean towards the point of view (object) of the apparatus rather than victims and perpetrators. Third, the media has a high motive for reporting warnings and exploitation motives. Based on the three results of the mapping of sexual violence reporting, the five online media tend to show injustice in writing reasons.